Coronavirus 2019 disease : are corticosteroids the key treatment? : a retrospective case-control study in Brazil - Rios, Salete da Silva (2022)
Background: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection is the putative cause of coronavirus disease 2019 (COVID-19), a serious disease that has severely impacted the world. Although vaccines have been developed, it will take time to inoculate the global population. Current guidelines have focused on the treatment of severe cases in hospital settings; however, a void has been created regarding appropriate measures for those in the initial stage of COVID-19 and those experiencing moderate disease severity progressing to desaturation. We assessed clinical outcomes in patients with COVID-19 with pneumonia at initial presentation treated with corticosteroids. Methods: Data of 177 consecutive high-risk patients with COVID-19, monitored by telemedicine, were collected and analyzed. Of those, 68 patients were in the initial inflammatory phase of the disease without desaturation and received corticosteroids. The outcomes were evaluated after a follow up of 14 days. Four patients were immediately referred to the hospital because they had explicit desaturation at presentation. Results: After 14 days, all patients in the inflammatory phase at presentation who were treated with corticosteroids before desaturation were alive and without complications. However, of the four patients with desaturation, one died at the hospital. Conclusion: In this study, the use of corticosteroids during the initial pulmonary phase of COVID-19 before desaturation, in addition to daily monitoring of patients, prevented disease progression, decreased the risk of complications and incidence of hospitalization and death. However, additional studies with larger number of patients are needed to confirm these findings.